Democracia e orçamento participativo : um estudo de caso do município de Vila Velha - Tavares, André Luiz Souto (2018)
The figure of Participatory Budgets (PB) as an instrument of public deliberation is hailed not only for being able to make feasible some of the most central assumptions of the normative perspectives of democracies, but also as an object of political inclusion and. promotion of social justice. Based on the main variables mentioned in the academic as determinants of the success of PBs (institutional design, associativismo and government commitment), the objective of this research is to analyze the relationship between these variables to understand the experience of elaborating the participatory budget in the municipality of Vila Velha for the biennium 2017-2018. In order to do so, it used information from academic papers, official documents, interviews with OP actors and, as a complement to these sources, the use of participatory observation method at OPVV assemblies and meetings. Despite the lack of clarity in the definition of criteria for filtering viable actions between the OPVV phases, the analysis of the variable government commitment showed a commitment of the administration with all phases of the process of preparing the OPVV, so that there was a significant effort in the realization of the micro-regional assemblies in the neighborhoods, as well as the attempt to include the population not present in the meetings in the process of participation with the implementation of the Participatory Budget online. With regard to local associativism, it was a low level of community organization at the context of OPVV, despite the historical and relevant associative tradition in the municipality, especially in the 1970s and 1980s, with popular movements that demanded improvements conditions for population in general. Given a context in which the government vector supplants the forces originating from civil society, there is a process of construction of the institutional design that is not always permeable by democratic relations that favor equality and equity in the process of elaboration of the OPVV.